CIRCULATING LEUCINE-RICH α-2-GLYCOPROTEIN glycoprotein 1 TO DETECT ACUTE APPENDICITIS IN PATIENTS WITH ACUTE ABDOMINAL PAIN. Issue 9 (14th August 2014) - Rainer, Timothy H; Leung, Ling Yan; Chan, Pui Yee Cangel; Leung, Yuk Ki; Lai, Bo San Paul; Cheung, Yue Sun; Graham, Colin A
Abstract : Objectives & Background: Circulating leucine-rich α-2-glycoprotein-1 (LRG1) protein has been found in the plasma and urine of patients with acute appendicitis (AA) and may be useful for diagnosis. The present study aimed to investigate whether circulating LRGI mRNA levels also improve the early diagnosis of AA. Methods: A prospective study was conducted between December 2011 and October 2012 on patients presenting to the ED with acute abdominal pain (<7 days of symptom onset). AA was confirmed if there were histopathological findings of an inflammed or necrotic appendix in appendicectomy specimens. Real-time polymerase chain reaction was used to analyze whole blood LRG1 mRNA level taken from these patients within 24 hours of arrival (mean 12.4 h). The primary outcome was AA. Results: Eighty-four consecutive patients (40 (47.6%) with AA and 44 (52.4%) without AA; mean age 35 years; 41.6% males) were recruited. Median whole blood LRG1 mRNA levels were higher in AA patients than in non-AA patients (2.2 (95% CI 1.3–2.6) vs 1.3 (95% CI 0.8–1.8)×10 5 copies/ml, p =0.0122). Of 40 AA patients, 13 (32.5%) were diagnosed as complicated AA, and had median LRG mRNA level higher than in patients with simple AA (3.2 (95% CI 2.2–4.1) vs 1.6 (95% CI 1.1–2.5)×10 5  copies/ml, p =0.0479). At a LRG1 mRNA cutoff of 1.9×10 5  copies/ml, the optimal sensitivity and specificity were 57.5% and 72.7% respectively. At this cutoff, the odds ratio for AA was 3.6 (95% CI 1.5–9.0; p =0.0047). Conclusion: Whole blood LRG1 mRNA levels may be useful to diagnose simple and complicated AA from other causes of abdominal pain. Acknowledgement: This research study was supported by a Direct Grant for Research from the Chinese University of Hong Kong (reference no.: 2041642) (HK$18000).